Randomized controlled trial comparing efficacy of conventional and new single larger dose of intra-articular viscosupplementation in management of knee osteoarthritis. (22nd September 2017) - Suppan, Vijaya Kumar L; Wei, Chew Yu; Siong, Tan Chin; Mei, Tew Mei; Chern, Wong Bor; Nanta Kumar, Vijay Kumar; Sheng, Kee Rong; Sadashiva Rao, Ashutosh
Background: Intra-articular hyaluronic acid (HA) injection is used in management of knee, hand and hip osteoarthritis. While HA injection is included in the list of evaluated therapies, its efficacy and optimum dosing still have no consensus. This study was conducted to explore the possibility of using single injection HA to increase patient convenience while maintaining the therapeutic efficacy. Methods: We present a prospective, open label, non-blinded, randomized controlled trial performed in accordance with guidelines in principles of good clinical practice. Block randomization was done for patients to receive either single 5 ml GO-ON injection or the conventional three injections of 2.5 ml GO-ON at weekly interval. Baseline Western Ontario McMaster University Osteoarthritis (WOMAC) scores were evaluated and recorded. All subjects were re-evaluated at 3 months and the WOMAC score recorded again as primary end points. Data analyses were performed with IBM SPSS Statistics for Windows software (version 21.0, IBM Corp, Armonk, New York, USA). Results: In the cohort of 127 patients, 33 were males and 94 females. The mean age was 59.1 years (standard deviation (SD) = 7.25) in single injection arm and 60.1 years (SD = 7.72) in triple injection arm. The two groups were recorded to have no significant difference in age ( p = 0.46) and Kellgren–Lawrence radiological grade ( p = 0.694). There was significant increase in the WOMAC scores from the baseline (pre-injection) to that recorded 3 months after injection ( p < 0.001) in patients of both groups. However, there was no statistically significant difference noticed in this clinical improvement between the two arms ( p = 0.889). Conclusion: The study shows single 5 ml dose regime comparing well with conventional three doses of 2.5 ml of intra-articular GO-ON HA injected at weekly intervals and confirms good efficacy, tolerability and safety of single larger dose of GO-ON knee intra-articular injection.